An unusual presentation of giant pancreatic pseudocyst in the parietal wall (Indian Journal of Case Reports, 2021)
A true cyst is a localized fluid collection covered by a capsule lined by epithelium, whereas, a pseudocyst does not consist specific lining of cells. We report one such case of a 37-year-old gentleman with giant pancreatic pseudocyst in the anterior abdominal wall which had developed secondary to acute necrotizing pancreatitis. A contrast-enhanced computed tomography scan showed a pseudocyst in the lesser sac and left pre-renal fossa. He was planned for exploration but within a month, he was at the emergency with yet another episode of gastric outlet obstruction with a huge hypogastric swelling compressing the stomach. The patient was resuscitated and immediately posted for exploratory laparotomy. To the surprise of surgeons, the lump was just below the umbilicus with whatsoever no relation with the pancreas. However, the expert opinion of the histopathologists suggested it to be a pseudocyst.